HPLC-DAD-ESI-MSn identification of phenolic compounds in cultivated strawberries from Macedonia - Kajdžanoska, Marina; Gjamovski, Viktor; Stefova, Marina (Society of Chemists and Technologists of Macedonia, 2010)
Strawberry fruits contain phenolic compounds that exhibit antioxidant, anticancer, antiatherosclerotic, antinflammatory and anti-neurodegenerative properties. High-performance liquid chromatography (HPLC) coupled to electrospray ionization mass spectrometric (ESI-MS) detection in the positive and negative ion mode has been used to identify the phenolic compounds in extracts from sixteen different strawberry cultivar fruits from Republic of Macedonia. Photodiode-array detection (DAD) has been used for screening of the different classes of phenolic compounds, whereas MS and MSn fragmentation data were employed for their structural characterization. The phenolic compounds identified were grouped as: ellagic acid and ellagic acid conjugates with sugars, ellagitannins, anthocyanins, flavonols, flavanols, and acylated sugars (feruloyl, caffeoyl and coumaroyl hexoses). Quercetin and kaempferol were the major flavonols found as quercetin 3-O-glucoside, quercetin 3-O-glucuronide, kaempferol 3-O-glucoside, kaempferol 3-O-glucoronide, kaempferol 3-O-malonylglucoside, kaempferol 3-O-acetylglucoside and kaempferol 3-O-coumaroylglucoside. Pelargonidin-3-O-glucoside was the most abundant anthocyanin in all strawberry extracts. Proanthocyanidins were also identified by MSn fragmentation as dimers, trimers and tetramers of (epi)catechin and (epi)afzelechin. This is the first assay of the phenolic profile of the strawberry cultivars in Macedonia, which can be further developed for characterization and evaluation of their quality with regards to their phenolic composition.